Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 7 - 7.1 - Using Fundamental Identities - 7.1 Exercises - Page 513: 40



Work Step by Step

We know that: $sin^2y+cos^2y=1$ $cos^2y=1-sin^2y$ So: $\frac{cos^2y}{1-sin~y}=\frac{1-sin^2y}{1-sin~y}=\frac{1^2-sin^2y}{1-sin~y}=\frac{(1+sin~y)(1-sin~y)}{1-sin~y}=1+sin~y$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.